Students’ Extensive Reading Through Digital Media in Learning English: Problem Based Learning (PBL) (A Critical Review) - Fetriani; Eki Saputra (Teaching English and Language Learning English Journal, 2024)
Extensive reading has been continuously studied as a promising instructional method for improving students’ language proficiency, including reading proficiency, vocabulary acquisition, and grammar awareness. However, this practice still presents many challenges due to several factors. hence, this paper aims to critically review students’ extensive reading through problem-based learning with digital media in learning English. The present study is a meta–analysis by focusing on the Students’ Extensive Reading used digital media in learning English: problem-based learning. This study used 15 articles related to students’ extensive reading, digital media and problem-based learning (PBL). It was revealed that the implementation of digital extensive reading through those various digital or online platforms has been proven to be useful in supporting the success of EFL students’ digital extensive reading activities as well as the success of EFL students’ language learning. By using PBL showed that there are differences in the subjects’ advanced reading proficiency level as well as an increase in empathy soft skill before and after the implementation of the learning method. The integration of digital media and problem-based learning in extensive reading ushers in a new and significant era of English education. It makes the students to develop as independent learners who can successfully negotiate the complexity of the global language in improving their language proficiency. Keywords: Problem-Based Learning, Extensive Reading, Digital Media